The demise of the Jane Addams Hull House Association : internal or external factors to blame? - Donnelly, Anne Cohn; Snyder, Charlotte ([London] : SAGE, 2016)
In January 2012, the Jane Addams Hull House Association stunned the philanthropic world when it laid off its employees without notice, declared its intention to liquidate in a Chapter 7 bankruptcy and shut its doors forever. In the weeks that followed, more and more people began to ask: What had happened to the board? Had bankruptcy really been inevitable? This case chronicles the organization's final decade and enables students to step into the shoes of the chairman of the board, Steve Saunders, as he led the board through its last two years.
Originally Published in: Donnelly, A. C., & Snyder, C. (2014). The Demise of the Jane Addams Hull House Association: Internal or External Factors to Blame? 5-114-003. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Hull House Association; Corporate governance -- Case studies; Nonprofit organizations -- Management -- Case studies